Effect of Addition of Dramix 3D Steel Fiber on Compressive Strength and Tensile Strength in Hpc (High-Performance Concrete) Concrete - Agustinus Simangunsong; Johannes Tarigan; Nursyamsi Nursyamsi; Ricky Bakara (Jurnal Indonesia Sosial Teknologi, 2024)
Concrete material is one of the most widely used construction materials in Indonesia due to its high compressive strength and adaptability to various construction needs. Despite its benefits, concrete has limitations, notably its weakness in tension and tendency to crack under tensile stress. This research focuses on High-Performance Concrete (HPC) with compressive strength exceeding 80 MPa, reinforced with 3D Dramix steel fibers to enhance both compressive and tensile strength. The study aimed to evaluate the compressive strength and splitting tensile strength of HPC mixed with varying percentages (0%, 3%, 6%, and 9%) of Dramix 3D steel fibers. Additionally, the methodology involved microstructure analysis using Scanning Electron Microscopy (SEM) and mechanical testing on HPC samples cured at 7, 14, and 28 days. Results indicate that the compressive strength reached a maximum of 94.776 MPa, and tensile strength reached 6.599 MPa with a 9% fiber addition at 28 days, highlighting the material's potential application in high-performance structural elements. The findings suggest that 3D Dramix steel fibers significantly enhance the mechanical properties of HPC, making it a viable option for durable construction.